Influence of integrity, independence, professional skepticism, and audit situation on audit opinion - Aulia, Rahma; Maulana, Agus; Supriadi, Taufiq (Badan Pemeriksa Keuangan Republik Indonesia, 2024)
In forming an audit opinion, some aspects need to be considered by state auditors. This study aims to investigate the impact of integrity, independence, professional skepticism, and audit situation on audit opinion in the context of auditing state institutions by state auditors. Cluster proportional sampling was used to sample 52 auditors who worked at the Directorate General of Audit I, BPK RI. The analysis was conducted using structural equation modeling and partial least squares with SmartPLS 4 software. The results revealed that integrity and independence positively affected audit opinion. Professional skepticism and audit situations do not affect audit opinion. The results will provide input to the BPK RI in guiding the development of auditor competencies to improve the quality of audit results. This study concludes that auditors believe that when they demonstrate integrity and independence, the accuracy of audit opinion will increase. This is because, with these qualities, an auditor will have courage, honesty, and responsibility and will not be unduly influenced. Although previous studies have extensively examined the impact of these factors in the context of audit firms auditing commercial companies, this is a novel study in the context of audits conducted by state auditors for state institutions.